Health-care costs of inflammatory bowel disease in a pan-European, community-based, inception cohort during 5 years of follow-up: a population-based study. (May 2020) - Burisch, Johan; Vardi, Hillel; Schwartz, Doron; Friger, Michael; Kiudelis, Gediminas; Kupčinskas, Juozas; Fumery, Mathurin; Gower-Rousseau, Corinne; Lakatos, Laszlo; Lakatos, Peter L; D'Incà, Renata; Sartini, Alessandro; et al.
Summary: Background: Inflammatory bowel disease (IBD) places a significant burden on health-care systems because of its chronicity and need for expensive therapies and surgery. With increasing use of biological therapies, contemporary data on IBD health-care costs are important for those responsible for allocating resources in Europe. To our knowledge, no prospective long-term analysis of the health-care costs of patients with IBD in the era of biologicals has been done in Europe. We aimed to investigate cost profiles of a pan-European, community-based inception cohort during 5 years of follow-up. Methods: The Epi-IBD cohort is a community-based, prospective inception cohort of unselected patients with IBD diagnosed in 2010 at centres in 20 European countries plus Israel. Incident patients who were diagnosed with IBD according to the Copenhagen Diagnostic Criteria between Jan 1, and Dec 31, 2010, and were aged 15 years or older the time of diagnosis were prospectively included. Data on clinical characteristics and direct costs (investigations and outpatient visits, blood tests, treatments, hospitalisations, and surgeries) were collected prospectively using electronic case-report forms. Patient-level costs incorporated procedures leading to the initial diagnosis of IBD and costs of IBD management during the 5-year follow-up period. Costs incurred by comorbidities and unrelated to IBD were excluded. We grouped direct costs into the following five categories: investigations (including outpatient visits and blood tests), conventional medical treatment, biological therapy, hospitalisation, and surgery. Findings: The study population consisted of 1289 patients with IBD, with 1073 (83%) patients from western Europe and 216 (17%) from eastern Europe. 488 (38%) patients had Crohn's disease, 717 (56%) had ulcerative colitis, and 84 (6%) had IBD unclassified. The mean cost per patient-year during follow-up for patients with IBD was €2609 (SD 7389; median €446 [IQR 164–1849]). The mean cost per patient-year during follow-up was €3542 (8058; median €717 [214–3512]) for patients with Crohn's disease, €2088 (7058; median €408 [133–1161]) for patients with ulcerative colitis, and €1609 (5010; median €415 [92–1228]) for patients with IBD unclassified (p<0·0001). Costs were highest in the first year and then decreased significantly during follow-up. Hospitalisations and diagnostic procedures accounted for more than 50% of costs during the first year. However, in subsequent years there was a steady increase in expenditure on biologicals, which accounted for 73% of costs in Crohn's disease and 48% in ulcerative colitis, in year 5. The mean annual cost per patient-year for biologicals was €866 (SD 3056). The mean yearly costs of biological therapy were higher in patients with Crohn's disease (€1782 [SD 4370]) than in patients with ulcerative colitis (€286 [1427]) or IBD unclassified (€521 [2807]; p<0·0001). Interpretation: Overall direct expenditure on health care decreased over a 5-year follow-up period. This period was characterised by increasing expenditure on biologicals and decreasing expenditure on conventional medical treatments, hospitalisations, and surgeries. In light of the expenditures associated with biological therapy, cost-effective treatment strategies are needed to reduce the economic burden of inflammatory bowel disease. Funding: Kirsten og Freddy Johansens Fond and Nordsjællands Hospital Forskningsråd.